14 The mechanism of pkcΒ-p66shc-nadph oxidase pathway in high glucose induced-oxidative stress in renal tubular epithelial cells. (5th December 2017) - Cheng, YS; Chao, J; Zhu, DD; Liu, BC
Abstract : Background: P66Shc is closely related to oxidative stress, but the exact mechanism of its involvement in diabetic nephro?pathy is poorly understood. Methods: In this study, molecular biological methods including western blot analysis, RNA interference, oxygen production measurement and apoptosis assay were applied to explore expressions and functions of P66Shc in damaged renal tubule epithelial cells (HK-2 cells) caused by high glucose levels. Results: Increased oxidative stress and up-regulated expression of P66Shc-NADPH oxidase and PKCβ were found in high glucose stimulated HK-2 cells. P66Shc-siRNA alleviated oxidative stress and apoptosis in damaged HK-2 cells. P66Shc-siRNA could significantly down-regulate the expression of NADPH oxidase, but had no effect on the high expression of PKCβ. As a PKCβ inhibitor, enzastaurin inhibited the expressions of p66Shc and NADPH oxidase. Conclusion: The study clarified a novel mechanism of oxidative stress damaging HK-2 cells via the modulation of the PKCβ-P66Shc-NADPH oxidase pathway. Understanding the molecular pathway of oxidative stress could translate into the development of therapeutic strategies for diabetic nephropathy. Acknowledgements: This work was supported by the National Natural Science Foundation of China [No. 81400300] and Natural Science Foundation of Jiangsu Province [No. BK20130642].